Exploring The Current Applications and Implications of Emerging Technologies for Digital Marketing - Genaro, Samuel; Rifiyanti, Hafizah (Universitas Muhammadiyah Surakarta, 2023)
With the development of internet and social media technologies, businesses are now able to interact with consumers directly and interactively through digital platforms, however, there is still a lack of understanding of the challenges and potential limitations faced by businesses in adopting and utilizing these technologies effectively. The purpose of this study is to gain a comprehensive understanding of the latest applications of emerging technologies for digital marketing, as well as to provide practical recommendations for companies to optimize the use of these technologies in digital marketing strategies. Data collection and analysis using a literature-based research approach. The rapid development of digital technology has influenced society in supporting various business activities in Indonesia, and many digital platforms help promote products to be sold or promoted. Although digital technology offers many benefits, it also presents challenges and risks. With the trend of digital marketing. This change shows that digital marketing has become a very effective medium for product promotion. By utilizing social media and digital marketing strategies, businesses can reach a wider target market, attract potential customers, and increase sales volume significantly. However, this also comes with challenges and risks. Data security and privacy are important considerations, especially when companies conduct online transactions and store customer data. This report emphasizes the importance of maintaining data security and privacy to build customer trust.